2019
DOI: 10.1080/15548627.2019.1635383
|View full text |Cite
|
Sign up to set email alerts
|

Disrupting the TRIB3-SQSTM1 interaction reduces liver fibrosis by restoring autophagy and suppressing exosome-mediated HSC activation

Abstract: Impaired macroautophagy/autophagy is involved in the pathogenesis of hepatic fibrosis. However, how aberrant autophagy promotes fibrosis is far from understood. Here, we aimed to define a previously unrevealed pro-fibrotic mechanism for the stress protein TRIB3 (tribbles pseudokinase 3)-mediated autophagy dysfunction. Human fibrotic liver tissues were obtained from patients with cirrhosis who underwent an open surgical repair process. The functional implications of TRIB3 were evaluated in mouse models of hepat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
75
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(81 citation statements)
references
References 51 publications
(58 reference statements)
0
75
0
Order By: Relevance
“…In this study, we identified Inhba and Dnmt3a as direct targets of miR-26a in the liver. Inhba can act as a promoter of various chronic liver diseases such as liver fibrosis and cirrhosis [61,62]. Dnmt3a has recently been shown to be an epigenetic regulator of insulin resistance [63].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we identified Inhba and Dnmt3a as direct targets of miR-26a in the liver. Inhba can act as a promoter of various chronic liver diseases such as liver fibrosis and cirrhosis [61,62]. Dnmt3a has recently been shown to be an epigenetic regulator of insulin resistance [63].…”
Section: Discussionmentioning
confidence: 99%
“…It is generally recognized that autophagy can have favorable and unfavorable outcomes in tumorigenesis and metastasis (40). Previous studies demonstrated that basal autophagy activation can modulate downstream signaling pathways that are involved in maintaining adequate HSC proliferation and differentiation (41). Impaired autophagy can result in the transformation of HSCs into a preleukemic state, increasing the likelihood of malignant leukemic transformation (42).…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy is an important strategy to maintain cell homeostasis (21). Autophagy is active in liver cells and maintains the normal physiological function of liver cells by eliminating easily accumulated proteins and damaged mitochondria (21)(22)(23). Additionally, autophagy is an important regulator implicated in various liver diseases (22).…”
Section: Discussionmentioning
confidence: 99%